2010
DOI: 10.1007/s11524-010-9439-3
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Respondent-Driven Sampling “Seed” Productive? Example of Finding At-Risk Massachusetts Men Who Have Sex with Men

Abstract: Several recent studies have sought to elaborate upon the applicability and validity of respondent-driven sampling (RDS) to find hard-to-reach samples in general and men who have sex with men (MSM) in particular. Few published studies have elucidated the characteristics associated with initial RDS participants ("seeds") who successfully recruited others into a study. A total of 74 original seeds were analyzed from four Massachusetts studies conducted between 2006 and 2008 that used RDS to reach high-risk MSM. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
(58 reference statements)
1
27
1
Order By: Relevance
“…Only the hypotheses regarding network size and stigmatization were supported. Although prior studies of adult MSM suggest that estimated network size may not be a significant productivity factor in RDS-based sampling, 19 we did find evidence to suggest it is an important factor among YMSM. More specifically, we found that controlling for other factors, YMSM with larger estimated eligible network (i.e., ≥10 people) may be up to 60 % more likely to recruit at least one additional person.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Only the hypotheses regarding network size and stigmatization were supported. Although prior studies of adult MSM suggest that estimated network size may not be a significant productivity factor in RDS-based sampling, 19 we did find evidence to suggest it is an important factor among YMSM. More specifically, we found that controlling for other factors, YMSM with larger estimated eligible network (i.e., ≥10 people) may be up to 60 % more likely to recruit at least one additional person.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of age, the homophily indices were positive and relatively low for both 16-18-year-olds and 19-20-years-olds (i.e., homophily indices of 0.26 and 0.16, respectively); estimated network size was slightly larger for younger participants (mean=6.1 for those ages 16-18 versus 5.3 for those ages [19][20]. Population estimates mirror these statistics with adjustment down in the younger group and up in the older group to account for differences in homophily and network size (i.e., 42.4 % ages 16-18 in the sample versus 37 % in the population, 57.6 % ages 19-20 in the sample versus 63 % in the population, respectively).…”
Section: Evaluation Of Respondent-driven Sampling In a Study Of Youngmentioning
confidence: 92%
See 3 more Smart Citations